PERTUMBUHAN DAN HASIL TANAMAN SAWI PUTIH (Brassica pekinensis L.) AKIBAT PEMBERIAN BERBAGAI DOSIS PUPUK KANDANG KAMBING - Neli Wahyuni; Edy Sofyadi (University of Insan Cendekia Mandiri, 2019)
This experiment has been carried out with the aim to get a good growth and yield of Chinese cabbage (Brassica pekinensis L.) as consequences of the application of various rate of goat manure fertilizer. This research has been conducted in the of Pusakamulya village, Kiarapedes district, Purwakarta Regency since January to July 2017. The environmental design used is a Randomized Block Design. Consisting of six treatments of goat manure dose: A = 0 g plant-1, B = 100 g plant-1, C = 200 g plant-1, D = 300 g plant-1, E = 400 g plant-1, and F = 500 g plant-1; each treatment was repeated three times. The results showed that the giving of fertilizer goat manure affected the growth and yield of Chinese cabbage (Brassica pekinensisL.). At goat manure fertilizer dose of 200 g plant-1gives a better influence on growth and yield of Chinese cabbage.